Validation study of a novel, rapid, open platform real-time LAMP assay for early diagnosis of pulmonary tuberculosis - Swathy S. Nair; Ria Elza Varghese; Anjana Saji; Anoopkumar Thekkuveettil (Scientific Reports)
Abstract Current nucleic acid amplification techniques for the diagnosis of pulmonary tuberculosis (TB) lack the simplicity and affordability of achieving the goals envisioned in the WHO END-TB strategy, particularly for low- and middle-income countries (LMICs). Here we report a cost-effective real-time LAMP (rt-LAMP) assay with high sensitivity for the early diagnosis of pulmonary TB. A sample size of 350 was calculated using Buderer’s formula. The assay was validated in the laboratory using mpt64 cloned gene targets and clinical patient samples. The lower limit of detection for the rt-LAMP assay was observed as 10 copies/µl. Out of 350 suspected TB patient samples, 47 were positive for MGIT culture (microbiological reference standard, MRS), 42 were positive for Xpert MTB/RIF and 41 were positive for rt-LAMP assay. Compared to MRS, rt-LAMP showed a sensitivity of 89.36% (95% CI 76.9–96.45%) and a specificity of 94.06% (95% CI 90.77–96.44%). When compared to Xpert MTB/RIF, rt-LAMP showed a sensitivity of 93.33% (95% CI 83.80–98.15%), a specificity of 98.62% (95% CI 96.51–99.62%), negative predictive value of 98.62% (95% CI 96.52–99.47%), positive predictive value of 93.33% (95% CI 84.07–97.38%). Youden index value of rt-LAMP was 0.92 when compared with Xpert MTB/RIF, indicating a significantly low false positive rate. As the technology has been developed in an open platform, the assay will be useful in early diagnosis of pulmonary TB, particularly in screening large susceptible populations in LMICs.